Experiences of Family Collaboration in Early Intervention among Korean and Chinese Caregivers - Kang, Veronica; Kim, Sunyoung; Wang, Jing (International Journal of Multicultural Education, 2023)
Despite the importance of family-centered practice in the Individuals with Disabilities Education Act Part C, a federally funded program for birth to two-year-old children with disabilities, there is a lack of research on Asian families who participate in early intervention in the U.S. This study examined the experiences of two Korean families and one Chinese family in early intervention in the U.S. Interviews were conducted and analyzed by bilingual researchers using ecological systems theory. As a multiple-case design study, the caregiver roles, beliefs, practices, and experiences related to their participation in early intervention were reported through within-case and cross-case analysis.